Task and Kinematic Parameters for Upper Limb Stroke Patient: A Review - Yosua Wijaya; Rifky Ismail; Toni Prahasto (Journal of Biomedical Science and Bioengineering, 2022)
The development of robotics technology has now been used to assist the rehabilitation therapy process of stroke patients.  This far, the progress of therapy patients has been observed qualitatively and quantitatively with several clinical assessments such as Fuegl Meyer, Barthel Index, Motor Function Index, etc. This paper aims to provide a review of stroke patient progress evaluation measurements using kinematic parameters using elbow and shoulder robotic therapy devices and provide an overview of the types of exercises performed on the robotic therapy interface on the motor and cognitive development of stroke patients. Thirty publications that used kinematic parameters as the basis for assessing the development of stroke patients were included, there were 81 kinematic parameters from all the studies reviewed, based on ICF 53 of which were included in the Body Functions and Structures (BFS) classification, and 28 others were included in the Activities and Participation (AP) classification. Several studies showed a good correlation between the measurement of kinematic parameters and clinical assessment (P<0.05), in addition to good correlation some kinematic parameters also showed good reliability (ICC, r>0.7; P<0.05).